PENENTUAN KONSTANTA DAN EKSPONEN PERSAMAAN TAYLOR PADA PROSES TURNING SEBAGAI PEDOMAN MENGETAHUI UMUR PAHAT KARBIDA - Ach. Kusairi S. (INFO-TEKNIK, 2014)
Product quality of a production process can not be separated from several other factors, including the planning and machining processes, which take place during the machining process there is interaction between the chisel work with the workpiece, the workpiece is cut off and the chisel work experience friction. As a result of this friction chisel wear out. Tool wear will be enlarged to a certain extent so that the cutting tool can not be used anymore. The length of time to reach the wear limit is defined as the tool life. Data on tool life is greatly needed in the planning process of machining a product. This study aims to determine the price constants (CT) and exponent (n) Taylor tool life equation in Turning Process with carbide Sculpture and Objects Work St 42, St 60 and Iron Castings and to determine the relationship between the input variables and the response variable from the observed process .The method used to determine the constants and exponents Equation Age Sculpture Taylor is a statistical method, while the statistical method is selected Linear regression analysis method to the calculation method of least squares or Least Squares Method. The study was conducted by observing the cutting conditions, where the cutting speed is varied the cutting speed ; v (m / min) selected three levels of cutting speed (v) is v1 = 37.68 m / min, v2 = 36.11 m / min, v3 = 34.54 m / min. Motion feeding also varied; f (mm / output) while eating the selected motion refers to the ability of the chisel is used and specification capabilities of the machine, the greater the speed selected eat, f1 = 0.25 mm / r and; f2 = 0.30 mm / r. Depth of Cut ; A (mm) made constant. Depth of cut selected; a = 1 mm.Getting research results, for the material St. 42 with f = 0.25 mm / put in can be CT = 65.92, n = 0.1737 are for f = 0.3 mm / put in can be CT = 72.4, n = 0.217. For Material St.60 with f = 0.25 mm / put in can CT = 57.5 n = 0.1482 are for f = 0.3 mm / put in can be CT = 47.68 n = 0.107. For material Iron Castings with f = 0.25 mm can be CT = 45.6 n = 0.107 are for f = 0.3 mm can be CT = 44.175 n = 0,103. The increase in cutting speed (v) is proportional to the occurrence of edge wear (VB). And at the same pace of growth will increase the wear edge is proportional to the time of cutting. The addition of the cutting speed and depth of cut motion meal will still result in the increase of the chisel edge wear so that tool life will decrease. Keywords: constants, Exponent, Equation Taylor, Turning Process, Age Sculpture